Influence of amylopectin structure and degree of phosphorylation on the molecular composition of potato starch lintners. Issue 3 (March 2014) - Wikman, Jeanette; Blennow, Andreas; Buléon, Alain; Putaux, Jean‐Luc; Pérez, Serge; Seetharaman, Koushik; Bertoft, Eric
ABSTRACT Morphology, molecular structure, and thermal properties of potato starch granules with low to high phosphate content were studied as an effect of mild acid hydrolysis (lintnerization) to 80% solubilization at two temperatures (25 and 45°C). Light microscopy showed that the lintners contained apparently intact granules, which disintegrated into fragments upon dehydration. Transmission electron microscopy of rehydrated lintners revealed lacy networks of smaller subunits. The molecular composition of the lintners suggested that they largely consisted of remnants of crystalline lamellae. When lintnerization was performed at 45°C, the lintners contained more of branched dextrins compared to 25°C in both low and intermediate phosphate‐containing samples. High‐phosphate‐containing starch was, however, unaffected by temperature and this was probably due to an altered amylopectin structure rather than the phosphate content. After lintnerization, the melting endotherms were broad with decreased onset and increased peak melting temperatures. The relative crystallinity was lower in lintners prepared at 45°C. A hypothesis that combines the kinetics of lintnerization with the molecular and thermal characteristics of the lintners is presented. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 257–271, 2014.